Therapy-Induced Growth and Sexual Maturation in a Developmentally Infantile Adult Patient with a PROP1 Mutation - Brunerova, Ludmila; Cermakova, Ivana; Kalvachova, Bozena; Skrenkova, Jana; Poncova, Renata; Sedlak, Petr (Frontiers in Endocrinology, 2017)
Background: Hypopituitarism as a result of PROP1 (Prophet of PIT1) mutation represents the most common genetic cause of combined deficiency of pituitary hormones and due to growth retardation it is typically diagnosed in childhood. Case Description: We present a unique case report of a prepubertal woman with growth retardation in whom combined pituitary hormone deficiency (central hypopituitarism, hypogonadism and growth hormone deficiency) caused by homozygous mutation c.150delA in the PROP1 gene was diagnosed late in young adulthood due to unfavorable life circumstances. Through cautiously combined growth hormone therapy and sex hormone therapy she has achieved better than expected height (exceeding predictions based on family height) and sexual maturation, including regular menstrual cycles. Conclusions: Early diagnosis of panhypopituitarism due to PROP1 mutation is essential for successful treatment; however, our case report shows that carefully titrated growth hormone treatment and sex hormone substitution, although initiated in adulthood, enable restoration of physiological growth and sexual development in a hormonally infantile adult woman with a PROP1 mutation.